Decrease of soil organic matter stabilization with increasing inputs: Mechanisms and controls - Shahbaz, Muhammad; Kuzyakov, Yakov; Heitkamp, Felix (Geoderma, 2017)
Crop residue addition is a way to increase soil organic matter (SOM) level in croplands. However, organic matter input and SOM stocks are not linearly related. Consequently, adding high amounts of residues, such as straw, may increase SOM to only a small extent, and an alternative use of the residues may be justified. The objective of this study was to test how the level and type (above- or belowground) of residue addition affect SOM stabilization. We hypothesise that (1) root residues will be mineralised slower than leaf and stalk residues, (2) soil aggregate formation will increase with high additions, and (3) wheat residue addition will induce positive priming, with the magnitude depending on the residue level and type. Homogeneously 13C-labelled wheat residues (leaves, stalks, roots) were added to a silt-loam soil at levels of 1.40 and 5.04gDMkg−1 and CO2 release and δ13C signature were measured over 64days at 20°C. Water-stable macroaggregates (>250μm), microaggregates (53–250μm) and silt plus clay size fractions (<53μm) were separated and 13C incorporation from residue was quantified in each fraction after 64days. Aggregate formation generally increased with added residue amount, but the proportion of residues occluded within aggregates decreased with increasing addition level. The occlusion of residues from aboveground biomass was more reduced with addition level than that of roots. Residue mineralisation increased with the addition level, but this increase was less for roots compared to stalks and leaves. Priming effects were similar between residue types and mainly depended on the added amount: SOM mineralisation increased by 50% and 90% at low and high addition levels, respectively. We conclude that the proportion of residues physically protected within aggregates decreases and priming effects increase with increasing C input leading to decreasing rate of long-term C stabilization within SOM by increasing residue addition. [Display omitted] •Aggregate formation increased generally with amendment level.•Decrease of residue occlusion with increasing inputs•Aboveground C retention in aggregates decreased at high level of addition.•Soil priming mainly depended on the level of addition.•Increased mineralisation and less residue physical protection decreased SOM stabilization.